Fabrication of Ba0.5Sr0.5Co0.8Fe0.2O3–δ Catalysts with Enhanced Electrochemical Performance by Removing an Inherent Heterogeneous Surface Film Layer. (20th November 2014) - Jung, Jae‐Il; Jeong, Hu Young; Kim, Min Gyu; Nam, Gyutae; Park, Joohyuk; Cho, Jaephil
<x xml:space="preserve">Abstract</x> A heat‐treatment approach for Ba0.5Sr0.5Co0.8Fe0.2O3–δ (BSCF5582) is introduced as a way of enhancing the electrocatalytic performance of perovskite catalysts. The perovskite made by heat‐treatment in oxygen atmosphere loses around 30 nm of spinel layer on the surface relative to the untreated version, and demonstrates enhanced oxygen reduction reaction and oxygen evolution reaction catalytic activities. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>